Probiotics and Preterm Infants: A Position Paper by the European Society for Paediatric Gastroenterology Hepatology and Nutrition Committee on Nutrition and the European Society for Paediatric Gastroenterology Hepatology and Nutrition Working Group for Probiotics and Prebiotics. Issue 5 (May 2020) - van den Akker, Chris H.P.; van Goudoever, Johannes B.; Shamir, Raanan; Domellöf, Magnus; Embleton, Nicholas D.; Hojsak, Iva; Lapillonne, Alexandre; Mihatsch, Walter A.; Berni Canani, Roberto; Bronsky, Jiri; Campoy, Cristina; Fewtrell, Mary S.; et al.
Abstract : ABSTRACT: More than 10, 000 preterm infants have participated in randomised controlled trials on probiotics worldwide, suggesting that probiotics in general could reduce rates of necrotising enterocolitis (NEC), sepsis, and mortality. Answers to relevant clinical questions as to which strain to use, at what dosage, and how long to supplement are, however, not available. On the other hand, an increasing number of commercial products containing probiotics are available from sometimes suboptimal quality. Also, a large number of units around the world are routinely offering probiotic supplementation as the standard of care despite lacking solid evidence. Our recent network meta-analysis identified probiotic strains with greatest efficacy regarding relevant clinical outcomes for preterm neonates. Efficacy in reducing mortality and morbidity was found for only a minority of the studied strains or combinations. In the present position paper, we aim to provide advice, which specific strains might potentially be used and which strains should not be used. In addition, we aim to address safety issues of probiotic supplementation to preterm infants, who have reduced immunological capacities and occasional indwelling catheters. For example, quality reassurance of the probiotic product is essential, probiotic strains should be devoid of transferable antibiotic resistance genes, and local microbiologists should be able to routinely detect probiotic sepsis. Provided all safety issues are met, there is currently a conditional recommendation (with low certainty of evidence) to provide either Lactobacillus rhamnosus GG ATCC53103 or the combination of Bifidobacterium infantis Bb-02, Bifidobacterium lactis Bb-12, and Streptococcus thermophilus TH-4 in order to reduce NEC rates. Abstract : Supplemental Digital Content is available in the text